Calcified versus non-calcified plaque volume fraction in patients with coronary artery disease and their association with outcome. (14th October 2021) - Kuneman, J H; Van Den Hoogen, I J; Schultz, J; Maaniiity, T; El Mahdiui, M; Kamperidis, V; De Graaf, M A; Broersen, A; Jukema, J W; Bax, J J; Saraste, A; Knuuti, J
Abstract: Background: The amount of coronary artery calcification is a general marker of coronary atherosclerosis and has been associated with increased risk of adverse cardiac events. On the other hand, calcification of coronary artery plaques has also been considered as a marker of plaque stabilization. Purpose: We hypothesized that the fraction of the non-calcified volume of the total plaque volume in patients with coronary artery disease (CAD) is associated with abnormal myocardial perfusion and increased risk of future cardiac events. Methods: Consecutive patients with suspected CAD undergoing sequential coronary computed tomography angiography (CCTA) with selective positron emission tomography (PET) perfusion imaging between 2007 and 2011 were selected. The total, calcified and non-calcified plaque volume (PV) were defined at patient-level. The non-calcified plaque volume fraction was calculated by dividing the non-calcified PV by the total PV, and expressed as percentage. Patients were divided into three groups: patients with 1) non-obstructive CAD (<50% diameter stenosis), 2) suspected coronary stenosis but normal PET perfusion and 3) suspected stenosis and abnormal regional PET perfusion. Difference between high vs. low PV was based on the median value. Clinical outcomes including all-cause mortality and myocardial infarction were recorded for 6.1 [SD 5.3–7.5] years. Results: In total, 494 patients (age 63±9 years, 55% male) with documented atherosclerosis on CCTA were included. Total PV, calcified PV and non-calcified PV were all significantly larger in patients with abnormal myocardial perfusion compared to patients with non-obstructive CAD (370 [197–739] mm 3 vs. 108 [59–177] mm 3, 84 [23–220] mm 3 vs. 9 [1–34] mm 3 and 274 [157–500] mm 3 vs. 94 [53–140] mm 3, respectively, p<0.001 for all). However, the non-calcified fraction was smaller in patients with reduced myocardial perfusion (75 [63–86]% vs. 89 [76–98]%, p<0.001, Figure 1). During follow-up 35 events occurred. Patients with higher total PV, calcified PV and non-calcified PV showed worse outcome compared to patients with lower PV (log-rank p<0.001, Figure 2). In contrast, patients with a lower non-calcified plaque volume fraction showed poorer outcome (log-rank χ 2 =5.54; p=0.019) even after adjusting for statin therapy or revascularization. Conclusion: We observed that higher volumes of any plaque component in general are associated with abnormal perfusion and increased risk of future cardiac events. In contrast, patients with a lower non-calcified plaque volume fraction showed poorer outcome. Funding Acknowledgement: Type of funding sources: None.